Patient Reported Outcomes After Radiation Therapy for Bone Metastases as a Function of Age: A Secondary Analysis of the NCIC CTG SC—Twenty-Three Randomized Trial. (April 2018) - Chow, Selina; Ding, Keyue; Wan, Bo Angela; Brundage, Michael; Meyer, Ralph M.; Nabid, Abdenour; Chabot, Pierre; Coulombe, Genevieve; Ahmed, Shahida; Kuk, Joda; Dar, A. Rashid; Mahmud, Aamer; et al.
Purpose: To explore the age difference in response and patient-reported outcomes in patients with cancer having bone metastases undergoing palliative radiotherapy. Methods: Patients completed the European Organisation for Research and Treatment of Cancer (EORTC) Quality-of-Life (QOL) Bone Metastases module (QLQ-BM22), EORTC QOL Core-15-Palliative (QLQ-C15-PAL), and Dexamethasone Symptom Questionnaire (DSQ) before a single 8-Gy radiation treatment, on days 10 and 42 after treatment. Patient demographics, performance status, analgesic consumption, BM22, C15, and DSQ were compared with multivariant analysis between patients under 75 years and 75 years and older. Multiple linear regression models were used to assess the differences between age-groups, adjusting for baseline demographics and primary disease sites. Results: There were 298 patients (170 male) with 209 (70%) less than 75 years of age. Most common primary cancer sites include lung, prostate, and breast. At baseline, younger patients had better performance status, consumed more analgesic, and reported worse scores in nausea, insomnia, and functional interference, while older patients more commonly had prostate cancer. There were no significant differences in the incidence of radiation-induced pain flare; response to radiation; changes from baseline for BM22, C15-PAL; and DSQ, nor overall survival at day 42 between the 2 groups. Responders to radiation in the elderly group reported better improvement in physical and emotional domains when compared with nonresponders. Conclusions: In patients with cancer having bone metastases undergoing palliative radiotherapy, there was no significant difference in general with age in response to radiation and patient-reported outcomes. Palliative radiotherapy should be offered to elderly patients when needed.